2022
DOI: 10.1186/s12917-022-03367-5
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular skeletal muscle mass assessment in dogs: a scoping literature review

Abstract: Background Monitoring changes in appendicular skeletal muscle mass is frequently used as a surrogate marker for limb function. The primary objective of this study was to review scientific information related to the assessment of appendicular skeletal muscle mass in dogs. The secondary objective was to develop practical recommendations for serial evaluation of muscle mass. Methods A scoping review was conducted with a systematic search of PubMed, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(264 reference statements)
0
3
0
Order By: Relevance
“…TMC measurement was used to assess limb muscle mass, reflecting the extent of limb usage and muscle development [29,30]. A higher TMC indicates a greater muscle mass, indicating a limb in better condition.…”
Section: Discussionmentioning
confidence: 99%
“…TMC measurement was used to assess limb muscle mass, reflecting the extent of limb usage and muscle development [29,30]. A higher TMC indicates a greater muscle mass, indicating a limb in better condition.…”
Section: Discussionmentioning
confidence: 99%
“…Limb girth measurement reliability overall has been considered questionable due to intra-and interobserver variation, patient positioning, or the variability in measurement devices used (Kim et al, 2022). To the authors' knowledge, although a landmark-incorporated limb girth measurement has been discussed by Kramer et al (2018), there are currently no peer-reviewed studies that have evaluated a landmark-incorporated limb measurement for evaluation of muscle mass in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an economical, non-invasive, and reproducible measurement that can be performed in a clinical setting within a short amount of time, like limb girth measurements, would be optimal for veterinary clinicians. However, a recent literature review reported that current techniques for limb girth measurements have been shown to be of questionable reliability (Kim et al, 2022). Previous studies have utilised landmarks, however, anatomical landmarks were used to identify the proximal and distal points to then calculate a percentage of distance at which the actual circumferential limb measurement will be obtained (Smith et To achieve a reproducible limb girth measurement, a technique with excellent reliability would be required.…”
Section: Discussionmentioning
confidence: 99%